Organisational readiness and Lean Thinking implementation: Findings from three emergency department case studies in New Zealand. (February 2014) - Rees, Gareth H
This paper describes and contrasts the implementation of Lean Thinking – a quality methodology that emphasises waste reduction and performing at higher levels of productivity with the same or less resources – into New Zealand's healthcare system. As the field is relatively new, three literature-based exemplar cases were developed to provide an analysis framework to analyse the three New Zealand research sites, which had activities, teamwork, leadership and sustainability as its core themes. Each research site's case was developed from primary data gathered through interviews, augmented by secondary data from project reports, District Health Board websites and media stories. The results highlight the benefits of a supportive quality-focussed organisational culture, executive management involvement and cross-functional teams as enablers. Further, work intensification and workplace resistance were also evident in varying levels within the sites. The study, while reiterating the problems of introducing quality methods from other domains into healthcare, presents the New Zealand context and reinforces that organisational preparedness as a significant factor which contributes to implementation success. This study goes beyond investigations of the use of Lean tools, changing improvement metrics and descriptive statistics to identify the contexts and variables which surround quality and process improvement implementations.